DESSB-TRNG: A novel true random number generator using data encryption standard substitution box as post-processing - Garipcan, Ali Murat; Erdem, Ebubekir (Academic Press Inc Elsevier Science, 2022)
In addition to providing hardware-dependent costly and slow solutions, statistical weakness is an important disadvantage of a cryptographic TRNG that is tried to be removed with post-processing techniques. In this study, the use of Data Encryption Standard (DES) substitution-box (s-box)-based post-processing method is proposed as an alternative solution to the problem of a physical TRNG's inability to generate cryptographic randomness discussed in detail. The proposed s-box-based post-processing method is applied in real time to a TRNG architecture based on two different digital noise source scenarios such as jitter and metastability on the Altera Cyclone GX FPGA chip. In both scenarios, the statistical quality of raw random numbers that s-box based transformations of 48x32 (48-bit input 32-bit output) are applied in the post-process stage is improved to meet the cryptographic competencies. This contribution of the proposed method has been analyzed and confirmed by statistical test techniques such as bias, entropy, correlation, and uniformity as well as National Institute of Standards and Technology (NIST) SP 800-22 randomness evaluation tests. In addition to the statistical analysis, the security analysis of the proposed method has been made and a detailed literature comparison of TRNG is presented by measuring the hardware performance parameters for both scenarios. All these analysis results confirm that the proposed method produces functional results for TRNG by providing a better trade-off in terms of design parameters such as security, area-energy consumption, compression rate, simplicity-applicability and hardware cost. The study is significant to showing that s-boxes with strong mathematical encryption features can be used for different cryptographic aims, such as random number generation, outside of the confusion function. (C)& nbsp;2022 Elsevier Inc. All rights reserved.
Keywords: TRNG; Post-processing; DES s-box; Jitter; Metastability